N6-methyladenosine modification of circNSUN2 facilitates cytoplasmic export and stabilizes HMGA2 to promote colorectal liver metastasis - Chen, Ri-Xin; Chen, Xin; Xia, Liang-Ping; Zhang, Jia-Xing; Pan, Zhi-Zhong; Ma, Xiao-Dan; Han, Kai; Chen, Jie-Wei; Judde, Jean-Gabrie; Deas, Olivier; Wang, Feng; Ma, Ning-Fang; et al. (Nature communications, 2019)
Circular RNAs (circRNAs) have been implicated in cancer progression through largely unknown mechanisms. Herein, we identify an N 6 -methyladenosine (m 6 A) modified circRNA, circNSUN2, frequently upregulated in tumor tissues and serum samples from colorectal carcinoma (CRC) patients with liver metastasis (LM) and predicts poorer patient survival. The upregulated expression of circNSUN2 promotes LM in PDX metastasis models in vivo and accelerates cancer cells invasion in vitro. Importantly, N 6 -methyladenosine modification of circNSUN2 increases export to the cytoplasm. By forming a circNSUN2/IGF2BP2/ HMGA2 RNA-protein ternary complex in the cytoplasm, circNSUN2 enhances the stability of HMGA2 mRNA to promote CRC metastasis progression. Clinically, the upregulated expressions of circNSUN2 and HMGA2 are more prevalent in LM tissues than in primary CRC tissues. These findings elucidate that N 6 -methyladenosine modification of circNSUN2 modulates cytoplasmic export and stabilizes HMGA2 to promote CRC LM, and suggest that circNSUN2 could represent a critical prognostic marker and/or therapeutic target for the disease. Liver metastasis of colorectal cancer leads to poor prognosis. Here the authors report that an N 6 -methyladenosine modified circular RNA is upregulated in colorectal cancer and promotes liver metastasis by enhancing the stability of HMGA2 mRNA.